Роль типа опыления в проявлении радиационно-индуцированной нестабильности генома у растений - Мамедли, С.А.; Гродзинский, Д.М. (Видавничий дім "Академперіодика" НАН України, 2007)
The radiation-induced genome instability of plants of tobacco Nicotiàna tabacum L. and onion Allium cepa L. is investigated. The increase of the amount of chromosomal aberrations in the plants of M1 and M2 is revealed. The level of chromosomal aberrations depends on the dose of irradiation and the method of plants pollination.